Justin S. Morrill papers - Morrill, Justin S. (Justin Smith), 1810-1898.
Correspondence, Senate and House reports and documents, remarks, speeches, invitations, newspaper clippings, pamphlets, and scrapbooks, chiefly 1854-1898, relating principally to Morrill's congressional career, especially the Morrill Tariff Act of 1861 and the original Land Grant College Act, and his positions on many Reconstruction issues. Correspondents include James Gillespie Blaine, Salmon P. Chase, L. E. Chittenden, Schuyler Colfax, Charles Dewey, Hamilton Fish, Horace Greeley, Jedidiah H. Harris, Charles Marsh, George Ward Nichols, Carroll Smalley Page, Henry Stephens Randall, A. N. Swain, Stephen Thomas, Adin B. Underwood, and Joseph Wharton.
Also available on microfilm
Microfilm produced from originals in the Manuscript Division.
U.S. senator and representative from Vermont and merchant.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Chittenden, L. E. -- 1824-1900 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Dewey, Charles, -- 1798-1880 -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Harris, Jedediah H. -- Correspondence; Marsh, Charles, -- 1765-1849 -- Correspondence; Nichols, George Ward, -- 1837-1885 -- Correspondence; Page, Carroll Smalley, -- 1843-1925 -- Correspondence; Randall, Henry Stephens, -- 1811-1876 -- Correspondence; Swain, A. N. -- Correspondence; Thomas, Stephen, -- 1809-1903 -- Correspondence; Underwood, Adin B. -- Correspondence; Wharton, Joseph, -- 1826-1909 -- Correspondence; United States. -- Congress. -- House; United States. -- Congress. -- Senate; Reconstruction (U.S. history, 1865-1877); School lands -- United States; State universities and colleges -- United States; Tariff -- United States; United States -- Politics and government -- 19th century; Vermont -- Politics and government -- 19th century; Merchants; Representatives, U.S. Congress -- Vermont; Senators, U.S. Congress -- Vermont